Housing Complex Jardim Redentor in Bauru, a Possible Example of Cluster - Oscalices, Gabriel Henrique; Ghirardello, Nilson (Latin American Journal of the Built Environment & Sustainability, 2025)
Objective – To analyze the urban design of Jardim Redentor I, the first housing complex built by COHAB Bauru, identifying its possible relationship with the cluster city concept developed by Alison and Peter Smithson, and assessing its uniqueness within the Brazilian context of the 1960s. Methodology – The research adopts an urban morphology approach, combining documentary analysis, literature review, and on-site observation to identify elements of identity, association patterns, growth, mobility, and clusters in the complex. Originality/relevance – The study addresses the theoretical gap regarding the application of postmodern concepts in social housing in Brazil during the hegemony of modernism, revealing the possible influence of avant-garde ideas in medium-sized cities in the interior of São Paulo state. Results – Jardim Redentor I presents an innovative and experimental urban configuration, prioritizing public spaces and community interaction, in contrast to the functional and economically driven models predominant at the time. Theoretical/methodological contributions – The study advances the understanding of the adaptation of cluster city principles in Brazilian housing contexts, suggesting new perspectives for the analysis of complexes designed in that period. Social and environmental contributions – The study highlights the relevance of design strategies that foster social cohesion, a sense of belonging, and the qualified use of public spaces, contributing to the construction of more inclusive and sustainable urban environments.